የሰብል ተረፈ ምርት መኖዎች አያያዝና የስነ ምግብ በህሪያቸውን ማሻሻያ ዘዴዎች - Assefa, Getnet; Bezabih, Melkamu; Mekonnen, Kindu; Adie, Aberra; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate Smart Feed and Forage Innovations Training Workshop-Amharic